Genome-wide association studies and prediction of 17 traits related to phenology, biomass and cell wall composition in the energy grass Miscanthus sinensis - Slavov, Gancho T (The New phytologist, 2014)
© 2013 The Authors. New Phytologist © 2013 New Phytologist Trust.